Efficacy of sonic versus manual toothbrushing after professional mechanical plaque removal: A 6‐month randomized clinical trial. Issue 4 (13th August 2021) - Mensi, Magda; Scotti, Eleonora; Sordillo, Annamaria; Brognoli, Valentina; Dominici, Maria Paola; Calza, Stefano
Abstract: Aim: The aim of this study was to compare the efficacy of two brushing methods (manual vs. sonic) in terms of plaque control after a session of professional mechanical plaque removal (PMPR). Methods: Subjects with gingivitis underwent a session of PMPR and were randomly assigned to sonic (SB) or manual brushing (MB). Oral hygiene instructions were provided at baseline (BL), 2 (T0a), 4 (T0b) and 6 weeks (T1) and 6 months (T2). Plaque Index (PI), Gingival Index (GI) and bleeding on probing (BoP) were measured at BL, T1 and T2. The proportion of sites with PI, GI and BoP was modelled at site level using a negative binomial regression fitted via generalized linear mixed model accounting for intra‐patient correlation. Results: Thirty‐two subjects were selected, 16 assigned to each group and 31 completed the study. PI, BoP and GI were comparable at BL. At T1, PI was successfully maintained at 6.21% for SB and 22.81% for MB, while at T2 reached 11.34% for SB and 28% for MB, favouring the SB group ( p < 0.001). GI and BoP were significantly lower in the SB group at T1, with a BoP reduction for SB about 3 times higher than MB ( p < 0.001). These parameters then levelled at T2 between the groups, with BOP reaching 0.14% versus 0.05% ( p = 0.356) and GI 1.75% versus 3.52% ( p = 0.020). Conclusion: Sonic brushing seemed to maintain a lower PI score compared to a manual brush at 6 months. BoP and GI resulted comparable.